TRANSFORMING BIPA LEARNING: INTEGRATING CROSS-CULTURAL COMMUNICATION WITH TECHNOLOGY FOR CULTURAL DIPLOMACY - Refa Lina Tiawati; Suci Dwinita (LLDIKTI Wilayah X, 2024)
This study explores how integrating cross-cultural communication strategies with technology can revolutionize the teaching of Indonesian for Foreign Speakers (BIPA) and enhance its role as a tool for cultural diplomacy. The research analyzes the experiences of BIPA teachers and learners at two universities in West Sumatra involved in the Darmasiswa program. Data were collected through semistructured interviews, direct observations, and document analysis to uncover strategies for addressing cross-cultural challenges and the role of technology in improving learning effectiveness. The findings reveal that combining cross-cultural communication with technology-based media, such as interactive videos, gamification applications, and online learning platforms, enhances cultural understanding and learning motivation. Practical simulations, such as role-playing and cultural discussions, enable learners to grasp Indonesia's socio-cultural context more deeply. However, limitations in technological literacy among teachers and learners, as well as cultural gaps, remain significant challenges. This study highlights the need for comprehensive training for teachers to maximize the potential of technology in education and the development of inclusive, culturally oriented teaching materials. These strategies improve learners' language competencies and strengthen cross-cultural relationships, positioning BIPA as an effective instrument for Indonesia's cultural diplomacy in the digital era.